A Bore-Integrated Patch Antenna Array for Whole-Body Excitation in Ultra-High-Field Magnetic Resonance Imaging - Svetlana S. Egorova; Nikolai A. Lisachenko; Egor I. Kretov; Yang Gao; Xiaotong Zhang; Stanislav B. Glybovski; Georgiy A. Solomakha (IEEE Access)
The human body’s ultra-high field magnetic resonance imaging suffers from the inhomogeneity of the radio frequency magnetic field $B_{1}^{+}$ and the high-peak levels of SAR created in body tissues during transmission. Both issues are typically addressed in the research domain using a tight-fit local array of antenna elements attached to the body and driven with customized phases by multiple transmit channels. The same approach faces difficulties in fast and reliable SAR evaluation, precise positioning, and patient comfort in the clinical environment. Recently, a novel bore-integrated array of stripline antenna elements with substantial free space was introduced for whole-body imaging at 7 T, showing, however, insufficient transmission efficiency (the level of $B_{1}^{+}$ at the unit input power). This work aims to improve the efficiency of the bore-integrated array configuration, which, unlike the tight-fit configuration, may be beneficial for prospective clinical workflow. After analyzing the proposed solutions, particularly the stripline antenna arrays, we found that one of the main limitations is the high level of losses within the array element. We propose using patch antenna elements separated by compact dual-loop decoupling resonators to overcome this limitation. Comparing the proposed elements with striplines in the same bore-integrated eight-channel configuration, we demonstrate numerically and experimentally on the bench a transmit efficiency improvement at least 3 times depending on the excitation mode. Furthermore, the proposed array is shown to overcome both the stripline array and volumetric TEM coil in terms of SAR efficiency approaching the level of the state-of-the-art tight-fit array of fractionated dipole antennas. Our results support the feasibility of integrating multichannel transmit array coils into the bore liner of a 7 T system while compromising transmit efficiency and providing competitive SAR efficiency.